Generalized gradients, bid–ask spreads, and market equilibrium. (4th March 2019) - Flåm, Sjur Didrik
Abstract: This paper considers economies in which each agent valuates various goods by own generalized gradients . Taken together and appropriately scaled, the latter determine bid–ask spreads . When all such spreads are nil, market equilibrium prevails. Crucial for the arguments is a money commodity which denominates agents' rates of exchange or substitution. Equilibrium obtains when rates coincide across agents. The results may facilitate detailed modelling of market micro-structure, direct deals, and agent-based computations.